Impacts of electronic public procurement in the Portuguese construction sector: several years after implementation - Gomes, J. P. F.; Laureano, R. M. S. (Handbook of research on modernization and accountability in public sector management, 2018)
The adoption of fully electronic public procurement (EPP) systems is a requirement laid out in a group of European Union directives. These standards seek to improve the rationalization of resources (i.e., on an economics level) in public administration through the replacement of paper-based procedures with electronic services (i.e., e-services), thereby contributing to the growth of electronic government (i.e., e-government) in all member states. This chapter evaluates the impacts of EPP based on information and communication technologies. Research was conducted in Portugal, in which data on five companies operating on an international scale were examined for any organizational difficulties in the adoption of e-procurement. The findings include the positive impacts of following the objectives of the European Union directives in question. User satisfaction regarding EPP-related electronic platforms was also investigated.